The Self-Revelation of Taufiq al-Hakim in the Novel Himār al-Ḥakīm: A Carl Thompson Perspective: Kashf al-dhāt ‘inda Tawfīq al-Ḥakīm fī riwāyah Ḥimār al-Ḥakīm: Ru’yah Carl Thompson - Chilwina, Nadhita; Kholil, Ahmad; Hasaniyah, Nur (An-Nahdah Al-'Arabiyah, 2025)
Self-image in real life is often shaped through the interaction between personal identity and social pressures that influence how one should act. Self-image in a social context is not something static, but rather a result of dynamic construction. This study aims to analyze the self-revelation of Taufiq Al-Hakim as both an author and a character in the novel Himār Al-Hakīm. This research is qualitative in nature, employing a library research method and using literary texts as the object of analysis. The data source used in this study is the Arabic novel Himār Al-Hakīm by Taufiq Al-Hakim, published by Maktabah Misr in 1990 (147 pages). The data collection technique used is reading and note-taking. The researcher applies the data analysis model from Miles and Huberman, which includes three stages: data reduction, data presentation, and conclusion drawing, using Carl Thompson’s travel literature theory as an analytical tool. This research reveals three main narrative forms in the novel Himār Al-Hakīm by Taufiq Al-Hakim:(1) Forms of reporting the world (4 data),(2) Forms of revealing the self (4 data), and (3) Forms of representing the others (5 data). The novel reflects characteristics of postcolonial travel writing through subjectivity, self-reflection, and a quest for identity. Al-Hakim blends autobiographical elements with an entertaining and reflective style, while also engaging in othering by portraying Eastern culture as inferior and Western culture as superior.   تتكون صورة الذات في الحياة الواقعية غالبًا من خلال نتائج التفاعل بين الهوية الشخصية والضغوط الاجتماعية التي تؤثر على كيفية تصرف الفرد. إن صورة الذات في السياق الاجتماعي ليست شيئًا ثابتًا، بل هي نتيجة لبناء ديناميكي. تهدف هذه الدراسة إلى تحليل صورة الذات لطه حسين ككاتب وشخصية في رواية "حمار الحكيم". هذه الدراسة هي بحث نوعي باستخدام منهجية البحث المكتبي، التي تستخدم النص الأدبي كموضوع للتحليل. تعتبر رواية "حمار الحكيم" التي كتبتها توفيق الحكيم (مكتبة مصر، 1990، 147 صفحة) هي مصدر البيانات المستخدمة في البحث. التقنية المستخدمة لجمع البيانات هي تقنية القراءة والتدوين. تطبق الباحثة نموذج تحليل البيانات من مايلز وهوبيرمان، الذي يتضمن ثلاث مراحل: تقليص البيانات، عرض البيانات، واستخلاص النتائج باستخدام نظرية أدب الرحلات لكارل طومبسون كأداة تحليل .يكشف هذا البحث عن ثلاثة أشكال سردية رئيسية في رواية "حمار الحكيم" لتوفيق الحكيم (1): أشكال سرد العالم (4 بيانات)، (2) أشكال كشف الذات (4 بيانات)، (3) أشكال تمثيل الآخر (5 بيانات) .تعكس الرواية سمات أدب الرحلات في فترة ما بعد الاستعمار من خلال الذاتية، والتأمل الذاتي، والسعي وراء الهوية. يمزج الحكيم بين عناصر السيرة الذاتية وأسلوب شيق وتأملي، مع الانخراط في تجسيد الآخر من خلال تصوير الثقافة الشرقية على أنها أدنى، والثقافة الغربية على أنها متفوقة.   Gambaran diri dalam kehidupan nyata sering kali terbentuk melalui hasil interaksi antara identitas personal dan tekanan sosial yang memengaruhi bagaimana seharusnya seseorang bertindak. Gambaran diri dalam konteks sosial bukanlah sesuatu yang statis, melainkan hasil konstruksi yang dinamis. Penelitian ini bertujuan untuk menganalisis gambaran diri Taufiq Al-Hakim sebagai pengarang sekaligus tokoh dalam novel Himār Al-Ḥakīm. Penelitian ini merupakan penelitian kualitatif dengan metode studi kepustakaan (library research), yang menggunakan teks sastra sebagai objek analisis. Sumber data yang digunakan dalam penelitian adalah novel Arab berjudul Himār Al-Ḥakīm karya Taufiq Al-Hakim, diterbitkan oleh Maktabah Misr pada tahun 1990 dengan jumlah 147 halaman. Teknik pengumpulan data yang digunakan adalah teknik baca dan catat. Peneliti menerapkan model analisis data dari Miles dan Huberman, yang mencakup tiga tahapan: reduksi data, penyajian data, dan penarikan kesimpulan, dengan menggunakan teori sastra perjalanan Carl Thompson sebagai pisau analisis. Penelitian ini mengungkap tiga bentuk naratif utama dalam novel Himār Al-Ḥakīm karya Taufiq Al-Hakim: (1) Bentuk peliputan dunia (4 data), (2) Bentuk pengungkapan diri (4 data), dan (3) Bentuk representasi orang lain (5 data). Novel ini mencerminkan karakteristik penulisan perjalanan pascakolonial melalui subjektivitas, refleksi diri, dan pencarian identitas. Al-Hakim memadukan unsur-unsur autobiografi dengan gaya yang menghibur dan reflektif, sekaligus terlibat dalam upaya pengasingan dengan menggambarkan budaya Timur sebagai inferior dan budaya Barat sebagai superior.